Opportunistic screening for osteoporosis using computed tomography scans and its comparison with DXA findings: a two-center cross-sectional study - Farzaneh Khoroushi; Ehsan Keykhosravi; Mohammad Taghi Shakeri; Masoumeh Salari; Ehsan Hassan Nejad; Asma Payandeh; Omid Salarzaei (Egyptian Rheumatology and Rehabilitation, 2024)
Abstract Background Osteoporosis is a prevalent condition leading to an increased risk of bone fractures. Osteoporosis poses a worldwide public health concern, impacting over 200 million individuals and resulting in a staggering 1.66 million hip fractures each year. Opportunistic osteoporosis screening can be employed during CT scans to assess bone mineral density (BMD) through Hounsfield units (HU) without the need for additional imaging, radiation exposure, or appointments. This study aimed to investigate a CT scan's diagnostic value in the opportunistic osteoporosis screening through L1 vertebra densitometry and compare it with dual-energy x-ray absorptiometry (DXA) findings. Results One hundred forty-nine patients with an average age of 67.70 ± 10.94 years were included in the study. The age of osteoporotic patients was significantly higher than osteopenic (p = 0.001) and normal individuals (p < 0.001). The HU of osteoporotic patients was found to be significantly lower compared to both osteopenic (p = 0.023) and normal individuals (p < 0.001). According to the ROC curve for osteoporosis prediction using the HU (AUC = 0.793 and p < 0.001), with a cut-off of 103 HU, the CT scan had a sensitivity of 69% and a specificity of 74% for the diagnosis of osteoporosis. Conclusion Individuals with osteoporosis exhibit a significantly lower average HU compared to both osteopenic and healthy individuals. A CT scan can serve as an effective predictor of osteoporosis in patients. The CT images obtained for reasons unrelated to osteoporosis diagnosis can be employed to discern patients with osteoporosis without incurring the added cost or radiation exposure.